2019
DOI: 10.1371/journal.pmed.1003002
|View full text |Cite
|
Sign up to set email alerts
|

Opioid-related treatment, interventions, and outcomes among incarcerated persons: A systematic review

Abstract: BackgroundWorldwide opioid-related overdose has become a major public health crisis. People with opioid use disorder (OUD) are overrepresented in the criminal justice system and at higher risk for opioid-related mortality. However, correctional facilities frequently adopt an abstinence-only approach, seldom offering the gold standard opioid agonist treatment (OAT) to incarcerated persons with OUD. In an attempt to inform adequate management of OUD among incarcerated persons, we conducted a systematic review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
95
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 76 publications
(278 reference statements)
4
95
2
4
Order By: Relevance
“…For these subjects, incarceration can constitute an opportunity to initiate an OAT [10]. Compared with the incarcerated subjects with OUD who are untreated, those who receive an OAT show signi cant reductions in their overall opioid use during incarceration, as well as in their injection behaviors, prison infractions, and suicide and overall mortality risk in prison [11,12]. Moreover, the treated subjects are less likely to experience an overdose after prison release.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these subjects, incarceration can constitute an opportunity to initiate an OAT [10]. Compared with the incarcerated subjects with OUD who are untreated, those who receive an OAT show signi cant reductions in their overall opioid use during incarceration, as well as in their injection behaviors, prison infractions, and suicide and overall mortality risk in prison [11,12]. Moreover, the treated subjects are less likely to experience an overdose after prison release.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the treated subjects are less likely to experience an overdose after prison release. Consequently, it has been deemed crucial to scale up OUD treatment and prevention strategies within a continuum of initiatives before, during, and after incarceration [12]. Despite this overall statement, the access to OATs remains globally insu cient in prison.…”
Section: Introductionmentioning
confidence: 99%
“…Within Canada, both in provincial and federal correctional settings, injection drug use prior to incarceration was commonly reported, with 2/3 of federal inmates reporting a history of substance use problems 8 . Several studies have found that in the rst weeks following release from prison, risk of non-fatal overdose and overdose death is markedly increased, and overdose is one of the leading causes of death related to correctional institutions both during and after incarceration 3,4,5 . In Canada, there have been fewer studies relating overdose death and incarceration history.…”
Section: Introductionmentioning
confidence: 99%
“…As far as protective factors, many studies have identi ed the availability of harm reduction during incarceration as having a protective effect on overdose deaths post-release. A 2019 systematic review found that opioid agonist treatment (OAT) provided to incarcerated people with opioid use disorder (OUD) reduces overdose incidence and mortality and improved retention rates in treatment services post-release 5 . It also recommended that OAT as well as other harm reduction strategies, including naloxone training and provision, be available before, during and after incarceration to reduce risk of overdose 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation